The Political Economics Side of the J-Curve - António Caleiro (Universidade de Évora, Departamento de Economia, 2008)
About twenty years ago, an article by van der Ploeg analysed the implications of the J-curve effect for the political business cycle in a small open economy [van der Ploeg (1989c)]. It was them shown that a sudden jump on the exchange rates in the election day should be observed if the government, in order to maximise its popularity, explores a J-curve effect. As a way of celebrating this work, that should have been more influential, i is presented in the paper a simulation study, which confirms the overvaluation result a la van der Ploeg.
Keywords: E31; E32; F31; 330; Exchange Rates; J-Curve; Partisan Business Cycles; Political Business Cycles